THE IMPACT OF THE COVID-19 PANDEMIC ON MENTAL HEALTH OF MEDICAL STUDENTS: GENDER ASPECTS - Nataliia Inshyna; Inna Chorna; Liudmyla Hrebenyk; Liudmyla Primova (Eastern Ukrainian Medical Journal, 2022)
Introduction. The COVID-19 pandemic and the resulting decline in social communication have negatively affected many people’s mental health, especially young people. This research aimed to investigate the mental health of Sumy State University medical students during the Covid-19 pandemic. This study was conducted from September 2020 to May 2021. Materials and Methods. The second-year students of the Academic and Research Medical Institute of Sumy State University participated in the study – 100 female and 100 male students. The average age of the students was 18–22 years. The mental health of the medical students was examined using the Goldberg General Health Questionnaire (GHQ-28). The total scores for mental health, psychosomatic symptoms, anxiety, insomnia, social dysfunction, and depression were investigated. The experimental data were analyzed using PAST statistical software v4.05. The research was conducted in compliance with the WMA Declaration of Helsinki’s “Ethical Principles for Medical Research Involving Human Subjects” after obtaining consent from all participants. Results and Discussion. It was found that the COVID-19 pandemic caused mental health disorders in 63.5 % of medical students. There was no significant difference in the total GHQ score (> 8) between men and women. Social dysfunction occurred to be the most common mental health disorder in medical students. Somatic symptoms, anxiety, social dysfunction, and depression were observed in 37.5 %, 49 %, 64 %, and 14 % of medical students, respectively. The prevalence of social dysfunction and depression was higher in men than women. Conclusion. It was established that men experienced more significant disturbances in mental health than women during the COVID-19 pandemic.